Relations between views on ageing and perceived age discrimination: a domain-specific perspective. - Voss, Peggy; Wolff, Julia Katharina; Rothermund, Klaus (European Journal of Ageing, 2017)
), we examined reciprocal relations between views on ageing and perceived age discrimination. Cross-lagged models revealed that domain-specific views on ageing predict subsequent changes in perceived discrimination in corresponding domains: Negative views on ageing regarding personal competence, physical decline, and social interactions were associated with increases in perceived discrimination in the domains of work, medical care, and social life, respectively. However, we did not find evidence for a reciprocal effect of perceived age discrimination on views on ageing. In sum, results indicate that negative views on ageing act as self-fulfilling prophecies by predisposing people to categorize other people's behaviour as age discrimination or to act themselves in a way that might elicit ageist behaviour in others.